PENGEMBANGAN MODEL PENDIDIKAN NILAI-NILAI BUDAYA DI SMP BERBASIS TRADISI SENI BATIK KLASIK SURAKARTA - Sariyatun, Sariyatun (Paramita: Historical Studies Journal, 2013)
The objective of the study is to develop the educational model of cultural values based on the classical batikÃ¢â‚¬â„¢s Surakarta arts tradition in order to strengthen the nation characters and national identity. The research was done by using the research and development method. In collecting the data, the researcher conducted several ways, as follow: interview, library research, forum group discussion and classroom action research. The qualitative analysis was used for conducting the need analysis as the first step of research and development activity and the quantitative analysis and the quasi-experiment were done to get the validation model. The result of this study showed that cultural values taught in junior high school were same as the character building education as a whole. The implementation of each character buildings stood on its own of each subjects and could be inserted into the guidance and counseling subject and the civics subject. Moreover, it was, then, defined that the educational model of cultural values based on the classical batikÃ¢â‚¬â„¢s Surakarta arts tradition was integrated to the social science subject as the model development of the character building. Keywords: model, education, cultural values, classical batikÃ‚Â Penelitian bertujuan untuk mengembangkan model pendidikan nilai-nilai budayaÃ‚Â  di SMPÃ‚Â  berbasis TradisiÃ‚Â  Seni BatikÃ‚Â  KlasikÃ‚Â  Surakarta sebagai Upaya Penguatan Karakter Bangsa dan IdentitasÃ‚Â  Nasional. Untuk mencapai tujuan tersebut penelitian dilakukan dengan Research and Development. Data dikumpulkan melalui wawancara, metode simak, FGD, observasi, dan Penelitian Tindakan Kelas. Pada tahap penelitian pendahuluan dan pengembangan model digunakanÃ‚Â  analisis Kualitatif. Tahap validasi model digunakan eksperimen semu dan analisis Kuantitatif. Hasil penelitian menunjukkan pendidikan nilai di SMP implementasinya sama dengan pendidikan budi pekerti. Implementasi pendidikan budi pekerti pada masing-masing satuan pendidikan (SMP) belum ada kesamaan yakni berdiri sendiri sebagai mata pelajaran dan digabungkan dengan Bimbingan dan Konseling atau PKN. Untuk itu, di rumuskan Draf strategi dan model PNBBTBK (Pendidikan Nilai Budaya berbasis Tradisi Seni Batik Klasik) melalui Integrasi dalam pembelajaran IPS sebagai pengembangan model Pendidikan Budi Nilai Budaya. Kata Kunci: model, pendidikan, nilai budaya, batik klasik Ã‚Â  Ã‚Â